2018
DOI: 10.3389/fpls.2018.00991
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Plasma Membrane Proteins Interacting With Arabidopsis thaliana Flotillin 2

Abstract: Arabidopsis flotillin 2 (At5g25260) belongs to the group of plant flotillins, which are not well characterized. In contrast, metazoan flotillins are well known as plasma membrane proteins associated with membrane microdomains that act as a signaling hub. The similarity of plant and metazoan flotillins, whose functions most likely consist of affecting other proteins via protein–protein interactions, determines the necessity of detecting their interacting partners in plants. Nevertheless, identifying the protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 118 publications
(171 reference statements)
1
30
0
Order By: Relevance
“…The interaction of At FLOTs (or possibly also At HIRs) with the CW constituents is probably indirect, that is via other proteins, supposedly with the ones containing extracellular domains. In our previous study, we found several transmembrane proteins, such as receptor‐like kinases, aquaporins, ATPases or other transporters in the interactome of At FLOT2 (Junková et al , ). At FLOT2 and At FLOT3 also interact with At TBL36 (associomics.org), a homologue of transmembrane trichome birefringence protein which is necessary for proper cellulose composition of the CW (Bischoff et al , ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The interaction of At FLOTs (or possibly also At HIRs) with the CW constituents is probably indirect, that is via other proteins, supposedly with the ones containing extracellular domains. In our previous study, we found several transmembrane proteins, such as receptor‐like kinases, aquaporins, ATPases or other transporters in the interactome of At FLOT2 (Junková et al , ). At FLOT2 and At FLOT3 also interact with At TBL36 (associomics.org), a homologue of transmembrane trichome birefringence protein which is necessary for proper cellulose composition of the CW (Bischoff et al , ).…”
Section: Discussionmentioning
confidence: 93%
“…Similar effect was observed in mammalian homologues of flotillins in which hetero‐oligomerization is important for endocytosis provided by flotillin nanodomains (Neumann‐Giesen et al , ; Solis et al , ; Babuke and Tikkanen, ). Recently, we have revealed several PM proteins constituting the interactome of At FLOT2 (Junková et al , ). In addition, At HIRs were found to be a part of PM‐associated complexes, which also contained phospholipase Dδ, cytoskeletal proteins, heat‐shock proteins, clathrin chains, transporters or kinases (Ho et al , ; Qi and Katagiri, ).…”
Section: Introductionmentioning
confidence: 99%
“…In various plant genomes, flotillin homologs were identified. For instance, in Arabidopsis thaliana, there are three homologs that are detected in plasma membrane DRM [40].…”
Section: Flotillinsmentioning
confidence: 99%
“…In mammals, among others, endophilins, caveolins, and flotillins are important in clathrin-independent endocytosis events [reviewed in (Ferreira and Boucrot, 2018)]. There are three homologues of flotillin in Arabidopsis that localise on the plasma membrane; however, none of them has been well characterised to date (Junkova et al, 2018). Homologues of caveolin do not exist in plants and, as discussed before, a true functional orthologue of endophilins has not been identified yet, though SH3Ps could represent possible candidates.…”
Section: Discussionmentioning
confidence: 99%